Role of clinical trials in survival progress of American adolescents and young adults with cancer—and lack thereof. Issue 8 (18th April 2018) - Bleyer, Archie; Tai, Eric; Siegel, Stuart
Abstract: In the United States, adolescent and young adult (AYA) patients with cancer have the lowest clinical trial participation rate of all age groups and slower progress in survival improvement than younger patients. Ominously, AYA clinical trial participation has been steadily decreasing since 2010, except in 15–19 year olds and AYAs with acute lymphoblastic leukemia. In order to reverse the accrual trend, multiple changes are necessary, including convincing community oncologists to pursue clinical trials on behalf of their AYA patients and to have the new National Community Oncology Research Program and National Clinical Trials Network lead a coordinated effort to increase accrual.